2010
DOI: 10.1007/s13233-010-0812-6
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular honeycomb and columnar assemblies formed by self-assembly of coil-rod-coil molecules with a conjugated rod segment

Abstract: Rod-coil molecules with conjugated rod segments have a strong tendency to self-organize into a variety of supramolecular structures in the bulk state. This paper reports the synthesis and self-assembly behavior of coilrod-coil molecules consisting of three biphenyls linked through a vinylene unit as a conjugated rod segment and poly(ethylene oxide) (PEO) with a degree of polymerization of 12 and 17 coil segments. The self-assembling behavior of these materials, which was investigated by differential scanning c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The supramolecular nanostructures of rod–coil molecules can be precisely tuned by the cooperative effects of several molecular parameters such as the ratio of rod to coil segments, rod anisotropy and coil cross‐sectional area 17–23. Lee's group and others have reported that rod–coil block systems are able to self‐assemble into one‐dimensional lamellae, two‐dimensional columnar structures, discrete bundles, ribbons, vesicles, and so on, depending on the relative volume fraction of rod segments 24–29…”
Section: Introductionmentioning
confidence: 99%
“…The supramolecular nanostructures of rod–coil molecules can be precisely tuned by the cooperative effects of several molecular parameters such as the ratio of rod to coil segments, rod anisotropy and coil cross‐sectional area 17–23. Lee's group and others have reported that rod–coil block systems are able to self‐assemble into one‐dimensional lamellae, two‐dimensional columnar structures, discrete bundles, ribbons, vesicles, and so on, depending on the relative volume fraction of rod segments 24–29…”
Section: Introductionmentioning
confidence: 99%
“…It should be pointed out that the peak associated with the (002) reflection has the highest intensity, indicating that the supramolecular three‐dimensional layer structure is composed of an ABAB arrangement crystalline layer of the rod segments with in‐plane hexagonal packing of coil perforations. In our previous work, we reported the synthesis and self‐assembling behavior of a coil–rod–coil molecule, consisting of three biphenyls linked through a vinylene unit as a conjugated rod segment and PEO with a DP of 12 as coil segments ( f coil = 0.68) . This molecule self‐organizes into a HPL crystalline phase and into a liquid crystalline mesophase, rectangular columnar structure and oblique columnar structure.…”
Section: Resultsmentioning
confidence: 99%
“…Their experimental results revealed that these copolymers exhibit two different conformations on self‐aggregation of these systems, rod–rod–rod and coil–rod–coil, as a consequence of a controllable rod‐to‐coil transition of the polypeptidic helices . In addition, for the past ten years, rod–coil molecules have been widely studied, with research focusing on rod segments consisting of different numbers of benzene rings, which are connected through ester bond, ether bond and CC double bond . Lee's group and others reported that a series of functional rod–coil block molecules consisting of three biphenyls connected through vinylene linkages as a conjugated rod segment, and poly(propylene oxide), poly(ethylene oxide) (PEO) or aliphatic polyether dendritic wedges with different cross‐sections as the coil segments self‐assemble into lamellar, hexagonal perforated lamellar (HPL), columnar and body‐centered tetragonal nanostructures .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in our previous work, we have reported the self-assembly of coil-rod-coil triblock molecules consisting of three biphenyls connected through vinylene linkages as a conjugated rod segment and poly(ethylene oxide) with a degree of polymerization of 12 and 17 as the coil segment (molecules 2b and 2c , see Scheme 1 ) [ 28 ]. The results of structural analysis indicate that these molecules spontaneously self-organize into a 3-D hexagonally perforated layer (HPL) structure and a 2-D rectangular or an oblique columnar structure in the crystalline and liquid crystalline phases, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…To further investigate the influence of methyl groups at the surface of rod and coil segments for construction ordered supramolecular nanostructures [ 15 , 28 , 29 ], in this study, we designed and synthesized coil-rod-coil molecules consisting of three biphenyls linked through a vinylene unit as a conjugated rod segment and poly(ethylene oxide) with a degree of polymerization of 7, 12 and 17, incorporating lateral methyl groups between the rod and coil segment as the coil segment. The self-assembling behaviors of 1a – 1c was investigated by means of differential scanning calorimetry (DSC), thermal polarized optical microscopy (POM) and X-ray scattering (XRD).…”
Section: Introductionmentioning
confidence: 99%